La tasa interna de retorno promedio borrosa: desarrollos y aplicaciones - Milanesi, Gastón S. (2016)
The paper introduces the average internal rate of return (AIRR) into the mathematic fuzzy’s frame, like alternative method for estimating returns in ambiguity situations. In the first part it is developed the AIRR and its fuzzy version like an alternative of return determination under ambiguity situations. Next, with a hypothetical case, the consistency with the present value (PV) in the projects ranking at conflictive situations is illustrated. In case of uncertainty,the equality between the AIRR estimated over the expected cash flows or as expected AIRR is showed. Finally, and like a measurement for estimating average returns in vague situations, it is set out the fuzzy AIRR, comparing results with the fuzzy PV and IRR methods. Doi: https://doi.org/10.1016/j.jefas.2015.12.001